Measles – Immunization Status and Outcome - Mahwish Rabia, Samiya Naeemullah, Asma Shabbir, Saima Kamran (Journal of Rawalpindi Medical College, 2014)
Background: To evaluate the immunization status, complications and clinical outcome in children admitted with measles. Methods : In this descriptive study 150 patients( 8 months to 12 years of age), with clinical diagnosis of Measles i.e. high grade fever, maculopapular rash, coryza, cough and conjunctivitis with its complications were included. Relevant information regarding age, sex immunization status and clinical presentation were also recorded. Immunization status of the patients was checked by examining the EPI card where available or parental enquiry if EPI card was not available. All the relevant investigations like CBC, serum electrolytes, X ray chest were carried out besides history and clinical examination. CSF examination was done where needed. All the patients were observed for complications like encephalitis, pneumonia, diarrhea, otitis media and corneal ulcers. They were managed according to the standard protocol of the hospital. Results: Of the 150 paediatric patients with diagnosis of measles included in the study, eighty nine(59.33%) were males. Mean age of the patients was 25 months. Seventy eight (52%) patients were well-nourished and 72(48%) were undernourished. Out of 150 patients 62% had received measles vaccine. Among vaccinated patients 5.33% patients had received two doses of measles vaccine and 85 had one dose. Majority (88%) developed complications. Pneumonia (43.33%) followed by diarrhea (23.33%) were the commonest. Six patients (4%) expired. Conclusion:There is a need to improve the nutritional status of the children and good coverage for the measles vaccine. The EPI needs to be strengthened.